2014
DOI: 10.1177/1071100714565177
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peroneus Brevis Tendon Anatomy on the Stability of Fractures at the Fifth Metatarsal Base

Abstract: Objectives:Fractures of the fifth metatarsal base are not uncommon. Both fracture management and outcomes can differ greatly depending on fracture location. The purpose of the present study is to evaluate the influence of the peroneus brevis (PB) tendon on proximal fifth metatarsal fracture stability. We hypothesize that proximal fifth metatarsal fractures distal to the PB tendon footprint are inherently less stable than more proximal fractures. Methods: We utilized 5 matched pairs of fresh-frozen cadaveric sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…It is conceivable that the morphologic characteristics of the bone may have been acquired after long-term mechanical stress due to age. Because the cadavers were preserved, biomechanical examination 24 could not be conducted. Another limitation was that the measurement in this study was made by only 1 examiner, however the intrarather reliability showed almost-perfect agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that the morphologic characteristics of the bone may have been acquired after long-term mechanical stress due to age. Because the cadavers were preserved, biomechanical examination 24 could not be conducted. Another limitation was that the measurement in this study was made by only 1 examiner, however the intrarather reliability showed almost-perfect agreement.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, risk factors for traction stress have not been fully elucidated, and it has been pointed out that traction stress may have an adverse effect on fracture incidence and healing. 24 If we could understand the characteristics of players with high traction stress and bending stress, it would be easier to identify players at high risk of Jones fractures.…”
mentioning
confidence: 99%
“…Typically, an acute injury to the fifth metatarsal is a result of indirect force secondary to foot plantar-flexion and inversion while the base of the fifth metatarsal is tethered by significant attachments to the calcaneus by the lateral band of the plantar aponeurosis, peroneus tertius tendon to the metaphysis and the peroneus brevis to the tuberosity. Peroneus brevis tendon forces contribute to the development of the Jones fracture and create a deforming force resulting in fracture instability and possible contribution to nonunion [8]. Additionally, bony malalignment of the foot may predispose patients to fifth metatarsal fractures.…”
Section: Mechanismmentioning
confidence: 99%
“…An early mobilization and return to competition is desired, but without compromising the stability of fracture fixation. Impaired healing response can be attributed to a compromised blood supply at the metadiaphyseal region [9,10], but mechanical instability may also play a detrimental role in Jones fracture healing [11][12][13]. It was postulated that early return to unrestricted sports activities might contribute to Level of evidence: Level II, controlled laboratory study Electronic supplementary material The online version of this article (https://doi.org/10.1007/s00264-020-04581-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the peroneus brevis during gait may potentially lead to displacement of the proximal fracture fragment in Zone II and III fractures, which are located distally to the PBT insertion. [1,11,18] Nevertheless, the role of the PBT as source of instability after Jones fracture fixation has been neglected so far. Early post-operative active mobilization may challenge the intramedullary stabilized Jones fracture by means of tensile forces which can lead to prolonged bone healing, or even result in early failure [11].…”
Section: Introductionmentioning
confidence: 99%